PEMBENTUKAN KEAHLIAN KEJURUAN DI INDUSTRI PERALATAN - Wicaksono, Padang; Priyadi, Lionel; Vitriano, Oscar (Jurnal Vokasi Indonesia, 2014)
After 1998 financial crisis, the growth of Indonesian manufactures sector had been dominated by the technology intensive- tools and machinery sub sector. The development of tools and machinery sub-sector should have increased the demand for skilled and specific labors namely vocational high school (VHS) graduates. Nevertheless, the VHS graduates’ roles had relatively been reduced. Despite they have better opportunities to develop their career in the long term, they are less likely to achieve supervisory or higher career level because the diploma or undergraduates workers most likely occupy the level. One of the main factors behind their lower career level prospects is due to rare opportunities to upgrade their skills through further On the Job Training in the shop floor. Coincidently, this arguably happened due to the declining position of Indonesian tools and machinery industry within global value chain from previously export oriented to domestic market oriented. Therefore, the existing technology transfer relatively hardly needs sophisticated skills which consequently could be delivered by less skilled workers such as general high school (GHS) graduates.